Global strategy for infant and young child feeding (WHO, 2003)
WHO and UNICEF jointly developed this global strategy to focus world attention on the impact that feeding practices have on the nutritional status, growth and development, health, and thus the very survival of infants and young children. The strategy is the result of a comprehensive two-year participatory process. It is based on the evidence of nutrition’s significance in the early months and years of life, and of the crucial role that appropriate feeding practices play in achieving optimal health outcomes. The strategy is intended as a guide for action; it identifies interventions with a proven positive impact, it emphasizes providing mothers and families the support they need to carry out their crucial roles, and it explicitly defines the obligations and responsibilities in this regards of governments, international organizations and other concerned parties.
Keywords: Infant Nutritional Physiological Phenomena; směrnice jako téma; veřejné zdravotnictví; zdravotní politika; pediatrie; National Health Programs; stravovací zvyklosti; fyziologie výživy kojenců; fyziologie výživy mladistvých; Child Nutritional Physiological Phenomena; Health Policy; Guidelines as Topic; Feeding Behavior; Breast Feeding; nutriční terapie, dietoterapie a výživa; Adolescent Nutritional Physiological Phenomena; kojení; fyziologie výživy dětí; programy národního zdraví